Tento seed germination and seedling emergence (Ormosia paraensis Ducke - Fabaceae) - Silva, B.; Silva, C.; Vieira, R. [UNESP]; Moro, F. [UNESP]; Drew, R. (Int Soc Horticultural Science, 2018)
Ormosia paraensis Ducke, known as tento, has seeds used to make handicrafts and wood worked by furniture makers. Despite its importance in handcrafted, timber and for the recovery of degraded areas, there is little research on the physiology of its seeds in order to help the production of seedlings in nurseries. Thus, the purpose of this research was to determine the temperature and the best substrate for the germination of seeds, as well as the substrate and sowing depth for tento seedling emergence. The range of the optimum temperature for seed germination is between 25 and 35 degrees C. Both sand and paper are suitable substrates for tento seed germination. Sowing depths higher than 2 cm are inadequate for Tento emergence. The most suitable substrates for seedling emergence in the nursery are sand, vermiculite and Plantmax (R).
Keywords: temperature; substrate; depth; Leguminosae